Smart Home Electric Energy Management Using Non-Intrusive Appliance Load Monitoring (NILM) - Nurman Hariyanto; Ary Setijadi Prihatmanto; Dian Anggraini (Journal of Software Engineering, Information and Communication Technology (SEICT), 2021)
Reducing the use of electrical energy in everyday life can be done with the awareness of the user. Awareness of using electrical energy can be done by providing information about the use of electricity itself. In developing a smart home with energy management systems or other commercial electronic devices, a tool that can measure or sort electricity usage in buildings and households is needed based on current and voltage units. Measuring and sorting what is meant is separating the total power consumption used as a load of a specific device that can be used by applying the Non-Intrusive Load Monitoring (NILM) technique known as Energy Disaggregation. The results are shown by NILM using the IoT concept data will be sent to the server via the internet using Message Queuing Telemetry Transport (MQTT). The data is processed and given to the user in the form of measurement results for each electronic device connected to the measuring device. From these results, the system can separate the energy from the refrigerator and air conditioner from the total energy consumed at one time. This step is one way to make energy efficient, that an energy management system with iot concept is built.